Fronteiras do medo: semelhanças produtivas e diferenças culturais em Ringu e o Chamado - Maciel, Filipe Tavares Falcão (2014)
Since the release of the film Ringu, in 1998, the Japanese contemporary horror cinema, or J Horror, became a filmic addressing form for the West. These Japanese horror movies have created a way of production that was soon "discovered" and exported by Hollywood through remakes for international audiences. The fact that the production of a remake will present differences between the original film and the new version is clear and doubtless. When these horror films are analysed as entertainment, it is possible to study much more than just filmic differences presented by cultural aspects. We developed our analysis in the perspective that there are reframings in the remakes of the movies as this means part of a productive logic way of the film industry as entertainment. In addition to the comparisons between Ringu and its American remake, The Ring, this research aims to develop the elements of production, distribution and exhibition as these three topics answer the aspects of the cinema as an industry. Through this triad, besides the cultural environment, it may be possible, for example, to find answers to suggest the changes we can notice in the remakes due to get an extension of an international audience as the original movie is usually released only in Japan.